KONSUMEN ANAK: Kajian Tentang Perlindungan Hukum Terhadap Lagu Dangdut Koplo Via Youtube - Budiono, Arief; Wardiono, Kelik; Puspita Sari, Arindra (JUSTISI, 2023)
This research, which aims to describe the legal protection of children as consumers of dangdut koplo songs, is based on legal research using a doctrinal approach. The main data in this study is in the form of secondary data obtained through a literature study of the dangdut koplo song which is broadcast via the YouTube platform. Based on the discussions that have been carried out, it is known that the dangdut koplo song still does not provide legal protection for children as song consumers, because it is contrary to Law Number 23 of 2002 concerning Child Protection. Keywords: dangdut koplo songs, child protection, consumers.